Legal Regulation of GMO Turnover and Health Protection in Russia - Alexandr Anatolievich Mokhov; Yury Alexandrovich Svirin; Vladimir Aleksandrovich Gureev; Natalya Semenovna Posulikhina; Sergej Nikolaevich Shestov (Institute of Medico-legal Publications Pvt Ltd, 2021)
The article considersboth advantages and disadvantages of the widespread use of genetically modified foodsamong the population. Special attention is drawn to insufficient arguments of their supporters and opponents. The authors of the article propose to focus on the possible advances and risks of genetically modified foodsfor public health. A state policy of approving or prohibiting the use of genetically modified foods, including the relevant bio-policy, should be based on the priority of human life and health and the interests of consumers of food products. Other arguments are secondary and subsidiary for making the most important political decisions affecting the foundations of human life and the environment. Methods: The research was carried out from the standpoint of theoretical analysis,general (sociological, systemic, structural, functional) and specialscientific methods (comparative jurisprudence, technical and legal analysis, specification, interpretation). The methodological basis of this study was the theory of knowledge.Objective: The article aims at studying the possibility of GMO turnover in Russia, as well as determining the purposes of their use and legal regulation.Results:It was concluded that the market authorization of genetically modified products and the issuance of appropriate permissions to use them as food products, whoseingredients contain a modified gene, make states answer the following question: “Do these genetically modified products preservepublic health and the health of a particular individual?”.If such a goal is not pursued, there is no social need (at least, in Russia) to introduce such products into civil circulation. Supporting this conclusion, the authors of the article provideseveralarguments